An introduction to hotel industry - Srivastava, Sanjiv Kumar; Srivastava, Praveen ;Shandilyav, Gautam (New Delhi, India : Trinity Press, 2018)
The ever growing demand of hoteliers in India and abroad has enticed the young talent to make their way towards Hotel industry. Keeping the need of these professionals and the new entrants in mind, an effort has been made to introduce the basics of Hotel industry in a simple and comprehensive way. The chapters highlight the importance of various departments in the Hotel industry, marking the difference between revenue producing and supporting department. Effort has been made to ensure that the book meets the demands of first year students of various catering colleges, apprentices and trainees working in hotels.
1.Hospitality industry -- 2.Departments in hotel -- 3.Front office organization -- 4.Organization of housekeeping-department -- 5.Cleaning equipment -- 6.Cleaning of guestroom -- 7.Cleaning of public areas -- 8.Introduction to cookery -- 9.Kitchen organization -- 10.Introduction to Indian cuisine -- 11.Food and beverage service industry -- 12.Organization of F & B service department -- 13.F & B service equipment -- 14.Methods of service -- 15.Menu planning -- 16.Beverages.
Includes index.
Keywords: HOTELS